The handbook of law and society - Sarat, Austin; Ewick, Patricia (Chichester, West Sussex, UK ; Malden, MA : Wiley-Blackwell, 2015)
Bringing a timely synthesis to the field, The Handbook of Law and Society presents a comprehensive overview of key research findings, theoretical developments, and methodological controversies in the field of law and society.
On the emerging maturity of law & society: an introduction / Patricia Ewick and Austin Sarat -- What is law and society? : definitional disputes / Susan M. Sterrett -- Charting the "classics" in law and society : the development of the field over the past half century / Calvin Morrill and Kelsey Mayo -- Mapping a cultural studies of law / Naomi Mezey -- Legal history / Kunal M. Parker -- Ethnographic and comparative approaches / Susan Bilder Coutin and Veronique Fortin -- Just a thought? : instantiations and constructions of procedural justice / Mary R. Rose -- Lawyers and the legal profession / Ronit Dinovitzer and Bryant Garth -- Courts and judges : the legitimacy imperative and the importance of appearances / Keith J. Bybee and Angela Narasimhan -- Jurors and juries / Nancy S. Marder -- Upside down and inside out : regulators and regulatory processes in contemporary perspective / Brownwen Morgan -- Using public law to shaper private organizations / Cary Coglianese and Jennifer Nash -- Police and policing / Jennifer Wood -- Law and the family / Annie Bunting -- Law & society perspectives on antidiscrimination law / Donna E. Young -- Law & society perspectives on punishment and social control / Keramet Reiter -- Welfare law / Vicki Lens -- Immigration law and immigrants : "lived experiences" / LeisyJ. Abrego -- The return of religion : the rise, decline, and possible resurrection of legal secularism / Nomi Maya Stolzenberg -- Human rights / Heinz Klug -- More than human legalities : advocating an "animal turn" in law and society / Irus Braverman -- Law and disability / Katharina Heyer -- The constitution of identity : law and race / Osagie K. Obasogie -- The constitution of identity : new modalities of nationality, citizenship, belongingand being / Eve Darian-Smith -- The past, present, and future of rights scholarship / Jeffrey Dudas, Jonathan Goldberg-Hiller, Michael McCann -- Law and social movements : old debates and new directions / Sandra Levitsky -- The rule of law and economic development : global scripts, vernacular translations / Ritu Birla -- Law in colonialism : legacies and lineages / Renisa Mawani -- Law and globalism : law without the state as law without violence / Julieta Lemaitre.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Law -- Social aspects; POLITICAL SCIENCE -- Government -- Legislative Branch; Law -- Social aspects; Electronic books; Electronic books